2008
DOI: 10.1002/chem.200701611
|View full text |Cite
|
Sign up to set email alerts
|

Application of MCD Spectroscopy and TD‐DFT to Nonplanar Core‐Modified Tetrabenzoporphyrins: Effect of Reduced Symmetry on Nonplanar Porphyrinoids

Abstract: The optical spectra of a series of core-modified tetrabenzoporphyrins were analyzed to determine the effects of core modification, ligand folding, and partial benzo substitution at the ligand periphery on the electronic structure by using magnetic circular dichroism (MCD) and NMR spectroscopy, X-ray crystallography, cyclic and differential pulse voltammetry, and TD-DFT calculations. Planar 21-carba-, 21-thia-, 21,23-dithia-, and 21-oxa-23-thiatetrabenzo[b,g,l,q]porphyrins reported previously were studied toget… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
41
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 55 publications
(44 citation statements)
references
References 49 publications
3
41
0
Order By: Relevance
“…Herein, our main strategy to try to meet these goals was to synthesize a series of core‐modified porphyrins in which the protonated pyrrole rings on the y axis were replaced by furan, thiophene, selenophene, and tellurophene moieties to form N 2 O 2 , N 2 S 2 , N 2 Se 2 , and N 2 Te 2 , respectively. Significant redshifting of the Q and B bands has been reported previously for core‐modified porphyrins 15. Because there are no fused phenanthrenes attached to the furan, thiophene, selenophene, and tellurophene moieties, there is a markedly lower degree of folding of the π‐system (Table 1).…”
Section: Resultssupporting
confidence: 52%
See 1 more Smart Citation
“…Herein, our main strategy to try to meet these goals was to synthesize a series of core‐modified porphyrins in which the protonated pyrrole rings on the y axis were replaced by furan, thiophene, selenophene, and tellurophene moieties to form N 2 O 2 , N 2 S 2 , N 2 Se 2 , and N 2 Te 2 , respectively. Significant redshifting of the Q and B bands has been reported previously for core‐modified porphyrins 15. Because there are no fused phenanthrenes attached to the furan, thiophene, selenophene, and tellurophene moieties, there is a markedly lower degree of folding of the π‐system (Table 1).…”
Section: Resultssupporting
confidence: 52%
“…The most‐widely applicable approach is the fusion of aromatic rings onto the β‐pyrrole carbon atoms. Although there have been a large number of reports on the effect of peripheral‐fused‐ring expansion on conventional tetrapyrrole porphyrins,14 the fused‐ring expansion of core‐modified porphyrins has only been studied to a limited extent 15. Herein, we report an in‐depth analysis of the optical properties of porphyrinoids with Group 16 heteroatoms, by replacing the two protonated pyrrole nitrogen atoms, and we explore the effect of fused‐ring‐expansion, the incorporation of additional pyrrole moieties, ligand nonplanarity, and the electron‐donating properties of meso ‐aryl substituents on their electronic structures.…”
Section: Introductionmentioning
confidence: 99%
“…As reported previously, the introduction of different fused‐ring moieties at the β‐carbon atoms of the pyrrole rings has a significant effect on the energies of the major electronic bands of porphyrins and their analogues (Figures and ), and this can be used to fine‐tune their optical and redox properties . For example, the Q(0,0) bands of 3 b lie at λ ≈600 nm, whereas the lowest energy bands of 3 c and 3 f , which have phenanthroline and acenaphthylene rings fused along the y axis, respectively, with benzene rings along the x axis, lie at λ ≈700 nm.…”
Section: Resultsmentioning
confidence: 79%
“…The trends observed in the UV/Vis absorption and MCD spectra are broadly reflected in the results of TD‐DFT calculations based on the use of the CAM‐B3LYP functional (Figure ). This functional is preferred because TD‐DFT calculations with the B3LYP functional are known to be problematic when significant charge‐transfer character is involved, and have been found to predict more intense bands at the blue end of the visible region and in the UV region of porphyrinoid spectra than those observed experimentally . This trend is also observed in the spectra of 3 a – g (Figure ).…”
Section: Resultsmentioning
confidence: 87%
“…Mack et al [17] demonstrated, based on an application of Michl's perimeter model [18] to the magnetic circular dichroism (MCD) spectroscopy and theoretical calculations of seventeen radially symmetric zinc porphyrinoids, that key trends observed in the spectral properties of porphyrinoids are largely determined by the relative energies of the four frontier p-MOs associated with Gouterman's 4-orbital model [19]. Recent studies on core modified tetrabenzoporphyrins [20] and a-phenylated phthalocyanines [21] have demonstrated that the results of DFT geometry optimizations are very similar to those obtained by X-ray crystallography when steric hindrance between peripheral fused rings results in severe ligand folding due to the lack of conformational flexibility. Trends observed in the experimental data for TPTPs can, therefore, be readily compared to those predicted in theoretical calculations for B3LYP optimized geometries even in the absence of X-ray structures.…”
Section: Introductionmentioning
confidence: 99%